Affective responses to supervised 10-week programs of resistance exercise in older adults - Darren L. Richardson; Michael J. Duncan; Alfonso Jimenez; Paul M. Juris; Neil D. Clarke (Elsevier, 2020)
Background: Resistance exercise has numerous, well-documented benefits on the health and functional performance of older adults. However, little information exists on the affective responses to resistance exercise in this population. As affective responses can predict continued exercise behavior, examining if and how they differ between resistance exercise intensities and frequencies in older adults may provide important data to improve resistance exercise prescription. Methods: We monitored the affective responses of older adults when performing high-velocity, low-load (HVLL) or low-velocity, high-load (LVHL) resistance exercise once or twice weekly. A total of 40 moderately to highly active, but resistance-exercise naïve, older adults (60-79 years) completed 1 of 4 randomly assigned progressive resistance exercise conditions: HVLL once weekly (HVLL1: n = 10), HVLL twice weekly (HVLL2: n = 10), LVHL once weekly (LVHL1: n = 10), or LVHL twice weekly (LVHL2: n = 10). The Physical Activity Affect Scale, Felt Arousal Scale, Feeling Scale, rating of perceived exertion, Visual Analog Scale, and the Physical Activity Enjoyment Scale were used to assess enjoyment and affective responses. Results: The results from Physical Activity Enjoyment Scale (out of 35) suggest that all exercise conditions were largely and similarly enjoyable to older adults (HVLL1: 30.9 ± 2.4; LVHL1: 31.9 ± 3.6; HVLL2: 30.9 ± 3.5; LVHL2: 30.2 ± 3.7) despite greater fatigue (p = 0.033; ηp2= 0.22) and perceived workload (p = 0.042; ηp2 = 0.20) in LVHL (results from Visual Analog Scale). Conclusion: Moderately to highly physically active older adults may tolerate higher intensities of resistance exercise performed once or twice weekly without experiencing a negative impact on enjoyment. However, the role that supervision and social interaction played in shaping the participants' responses is unclear.